Fighting for France : violence in interwar French politics - Millington, Chris, ca. 20./21. Jh. ca. 20./21. Jh (British Academy monograph, 2018)
'Fighting for France' is the first book to examine violence between political extremists in interwar France and the ways in which contemporaries understood it. This has important implications for understanding twentieth-century French politics, not least the French experience of collaboration with the Nazis during the Second World War